Dance in the R. J. Reynolds High School gymnasium. - Keith, Jim (Forsyth County Public Library, 2008)
Photo made in the 1960s.
Dance in the R. J. Reynolds High School gymnasium.
Keywords: Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works; Digital Forsyth